Causes of the Occurrence of Crime Gambling - Fajar Kesuma Derawan; Bastianto Nugroho (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The purpose of this research is to try and make people aware of the dangers posed by gambling. The research method uses normative juridical, based on the literature and case studies in the field related to the causes of the crime of gambling. The results of the development of Indonesian people's lives (Das Sein) can change legal arrangements regarding gambling from illegal to legal (Das Sollen) with certain conditions, namely that society must compare the impacts that will be caused by gambling and also prevent society from bad traits and will harm society itself. In order to reach crimes obtained from gambling, it seems that law enforcers in Indonesia must be brave in carrying out raids on gambling locations, so that objects obtained from crimes from gambling are either in the form of objects or valuables. In addition, law enforcers must order the payment of a sum of money to the perpetrators and players and bandits involved in gambling in terms of property previously confiscated. The amount of money that must be paid is balanced with the value of the object that should be seized.